A physico-mathematical model for solute transport in groundwater - Nguyen Phi Khu (Vietnam Journal of Mechanics)
In this paper a model for solute transport in groundwater, including physic-co-mathematical basis, numerical method some simple example simulations is briefly presented. This model has been gradually improved in both simulation and methodology.